Justification of parameters and numerical experimental studies of electrically heated floor - Романченко, Микола Анастасійович; Слесаренко, Анатолій Павлович; Сорока, Олександр Степанович (Technology audit and production reserves, 2013)
Algorithms and software solutions, which allow to ensure the optimum modes of power supply to the heaters of multilayer structured floor in rooms taking into account design and thermal parameters of electrically heated floor and peculiarly external meteorological factors, are proposed. The application of research results in production practice of specialized complexes will allow significantly improve the efficiency of using the traditional, alternative and renewable energy sources for ensuring the technological needs of livestock production. The proposed method allows at the stage of project development analyze and determine the geometric parameters and power characteristics of heat-generating modules of electrically heated floors of production facilities with various functional purposes. The managed mode of energy consumption by electric-heat-accumulating microclimate systems provides real conditions of energy consumption in the off-peak period of the daily load curve of electrical networks with reduced payment for energy under the zone tariff. Considerable heat-accumulating properties of electrically heated floors allow such systems to operate in the mode "consumer-regulator".